Evaluation of a Newly Identified Endophytic Fungus, Trichoderma phayaoense for Plant Growth Promotion and Biological Control of Gummy Stem Blight and Wilt of Muskmelon - Nuangmek, Wipornpan; Aiduang, Worawoot; Kumla, Jaturong; Lumyong, Saisamorn; Suwannarach, Nakarin (Frontiers in Microbiology, 2021)
Gummy stem blight and wilt are known to cause enormous losses to the global production of muskmelon (Cucumis melo). In this study, the potential of endophytic fungi isolated from leaves of Siam weed (Chromolaena odorata) was investigated for the inhibition of mycelial growth of Stagonosporopsis cucurbitacearum and Fusarium equiseti. Twenty-one fungal isolates were obtained. The results indicated that a fungal isolate UP-L1I3 displayed the highest percentage in terms of inhibition of the mycelial growth of F. equiseti and S. cucurbitacearum at 90.80% and 81.60%, respectively. Consequently, this isolate was selected for its potential ability to promote plant growth and control gummy stem blight and wilt in muskmelon seedlings. Morphological and multilocus phylogenetic analyses revealed that the isolate UP-L1I3 was a new species that has been described herein as Trichoderma phayaoense. Pathogenicity test confirmed that F. equiseti and S. cucurbitacearum were the cause of gummy stem blight and wilt disease in muskmelon seedlings, respectively. However, no disease symptoms were observed in seedlings inoculated with T. phayaoense. It was found that T. phayaoense could be used preventively in muskmelon seedlings that were inoculated with F. equiseti and S. cucurbitacearum, which could then reduce the impact on the disease severity index. Trichoderma phayaoense was also effective in improving plant development by increasing plant height, as well as shoot and root dry weight values. Moreover, T. phayaoense could effectively increase weight, diameter and the circumference and total soluble solid of fruit without having a negative effect on fruit quality parameters. Additionally, T. phayaoense was able to tolerate a commonly applied fungicide (metalaxyl) in recommended dosages for field applications.